Implementasi Manajemen Kurikulum Dayah Mudi Mesra Kabupaten Bireuen - Abd. Mukti; Syafaruddin Syafaruddin; Athahillah Athahillah (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2020)
The purpose of this research is to analyze the curriculum management of Dayah MUDI Mesra Bireuen Regency. The method used is qualitative research using interviews, observations and document studies. The results of this research are (1) Dayah curriculum planning is carried out by way of deliberation in preparing the curriculum. By involving dayah leaders, teachers and expert teams as well as the Ministry of Religious Affairs and the Dayah Education Development Office. The drafting mechanism is carried out by mapping basic competencies, analyzing time allocation, creating annual programs and semester programs, and then creating RPP; (2) Curriculum organizing shall be carried out with several activities through the division of teaching tasks in accordance with the areas of expertise and interests, preparation of lesson schedules, improvement and enrichment, extracurricular and refreshment schedules for teachers; (3) The implementation of a curriculum oriented towards the implementation of a productive, active, innovative, effective and enjoyable learning process (PAIKEM) is supported by dayah instructional leadership that exemplifies and motivates dayah teachers; (4) The supervision of the curriculum shall be carried out by the leadership on the implementation of learning conducted by the teacher based on the learning document and then supervision to the classroom during the learning; and (5) Curriculum evaluation includes examination of teacher learning documents/Learning Implementation Plan and capturing inputs related to the support system to improve the quality of dayah learning.